2019
DOI: 10.7759/cureus.3922
|View full text |Cite
|
Sign up to set email alerts
|

Use of Interventional Radiology in Critically Injured Children Admitted in a Pediatric Intensive Care Unit of a Developing Country

Abstract: ObjectiveThe aim of this study was to describe the outcome of the use of interventional radiological procedures (IRP) (angioembolization) in critically injured children.MethodsA retrospective review of medical records of all children who underwent an IRP from January 2010 to December 2015 was done. Data were collected on a structured proforma and results are presented as mean with standard deviation and frequency with percentages.ResultEighteen patients were identified who underwent IRP during the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In children, the use of primary hepatic AE has been reported rarely and is debated even in the presence of arterial blush where it seems to increase NOM failure rates [55], or according to some studies, it does not correlate with decrease odds of laparotomy [30]. In the pediatric population, AE use is associated with older age and is not completely defined in terms of efficacy and cost-effectiveness, especially in low-resource settings [30,[55][56][57][58][59][60][61]. Some authors, however, identify the presence of active contrast extravasation as an independent predictor for pseudoaneurysm (PSA) formation in children, regardless of injury grade.…”
Section: Diagnosismentioning
confidence: 99%
“…In children, the use of primary hepatic AE has been reported rarely and is debated even in the presence of arterial blush where it seems to increase NOM failure rates [55], or according to some studies, it does not correlate with decrease odds of laparotomy [30]. In the pediatric population, AE use is associated with older age and is not completely defined in terms of efficacy and cost-effectiveness, especially in low-resource settings [30,[55][56][57][58][59][60][61]. Some authors, however, identify the presence of active contrast extravasation as an independent predictor for pseudoaneurysm (PSA) formation in children, regardless of injury grade.…”
Section: Diagnosismentioning
confidence: 99%
“…In the literature, it was reported that 50 to 80% of laparotomies due to blunt liver trauma had no active bleeding and negative laparotomy was performed (22,23). Many studies have been managed to define specific criteria to facilitate the application of non-operative therapy and patient selection in cases with blunt trauma (1,24,25). These criteria were determined as hemodynamic stability, absence of peritoneal findings, less than 500 ml of hemoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright  Abbas Q post resuscitation HCMA in critically ill children. As lactic acidosis and hyperlactatemia are associated with high PICU mortality while hyperchloremia is result of isotonic fluid resuscitation [14,15]. So this debate of isotonic versus balanced salt solution in critically ill children continued [8] and till we have a final answer we should continue the use of isotonic saline for resuscitation as well as maintenance fluid therapy in critically ill children while carefully looking for the development of hyperchloremia.…”
Section: Gr Up Smmentioning
confidence: 99%